The validity of the Ligs digital arthrometer at different loads to evaluate complete ACL ruptures - Li, Junqiao; Tang, Jiexi; Yao, Lei; Fu, Weili; Deng, Qian; Xiong, Yan; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: The Ligs Digital Arthrometer is a recently launched versatile arthrometer that can be used for the quantitative assessment of knee and ankle joint laxity. This study aimed to evaluate the validity of the Ligs Digital Arthrometer for the diagnosis of complete anterior cruciate ligament (ACL) ruptures at different loads. Materials and Methods: From March 2020 to February 2021, we included 132 subjects diagnosed with complete ACL ruptures by magnetic resonance imaging (MRI) and eventually confirmed by arthroscopy and 114 normal subjects in the study. Anterior knee laxity was independently measured by the same physical therapist using the Ligs Digital Arthrometer. Recorded anterior knee laxity and calculated the side-to-side difference (SSD) at the loads of 30N, 60N, 90N, 120N and 150N, respectively. The receiver operating characteristic (ROC) curve was used to determine the optimal laxity threshold, and the diagnostic value was evaluated by the area under the curve (AUC). Results: The demographic data of the subjects were comparable between the two groups (p>0.05). The mean values of anterior knee laxity measured by the Ligs Digital Arthrometer between the complete ACL ruptures group and the control group were significantly different at all loads of 30N, 60N, 90N, 120N and 150N (p<0.001). According to the results of ROC curve analysis, the optimal laxity threshold for the diagnosis of complete ACL ruptures was 1.1mm SSD (Se=66.7%, Sp =69.3%) at 30N, 1.3mm (Se=74.2%, Sp=82.5%) at 60N, 1.6mm (Se=79.5%, Sp=94.7%) at 90N, 1.9mm (Se=84.1%, Sp=92.1%) at 120N and 2.1mm (Se=85.6%, Sp=91.2%) at 150N. The AUC order at different loads from high to low was 150N (0.948 [0.923~0.973])＞120N (0.933 [0.903~0.963])＞90N (0.902 [0.862~0.943])＞60N (0.846 [0.799~0.893])＞30N (0.720 [0.657~0.783]). Conclusions: The Ligs Digital Arthrometer was proved to be of high diagnostic value at 90N, 120N, and 150N loads for complete ACL ruptures. The diagnostic value improved with an increasing applied load in a certain range. Based on the results of this study, the Ligs Digital Arthrometer was a valid and promising diagnostic tool for complete ACL ruptures. Keywords：Anterior cruciate ligament; Knee laxity; Quantitative assessment; Ligs Digital Arthrometer; Diagnostic value